Defragmenting Struktur Berpikir Siswa SMP Dalam Menyelesaikan Masalah Bangun Datar - Mukhammad Ali Bahrudin; Nonik Indrawatiningsih; Zuhrotun Nazihah (IndoMath: Indonesia Mathematics Education, 2019)
This research purpose to description students’ error in solving problem of two dimension and effort defragmentation. Error analysis which execute base on concept construction error theory that include logical thinking error and hole contruction. This research done execute on students junior high school at eight grade of SMP in Pasuruan who finished two dimension material. Research subject is chose by students who are did mistake considerate of finishing comprehensiveness of students problem base Newman’s steps. From the result research was found that the students’ concept construction error in solving problem is erroring logic thinking and contruction hole. Defragmenting that id did by researcher is giving conflict cognitive to repar logic thinking error and appear scheme which still not build through scaffolding to hole that occur on students’ thinking structure.